The potential of intra-articular injection of chondrogenic-induced bone marrow stem cells to retard the progression of osteoarthritis in a sheep model - Al-Faqeh, Hamoud Hussien Mohammad; Mohamad Yahaya, Nor Hamdan; Chen, Hui Cheng; Saim, Aminuddin; Idrus, Ruszymah (2012)
In recent years, the use of bone marrow mesenchymal stem cell (BMSC) implantation has provided an alternative treatment for osteoarthritis. The objective of this study is to determine whether or not an intraarticular injection of a single dose of autologous chondrogenic induced BMSC could retard the progressive destruction of cartilage in a surgically induced osteoarthritis in sheep. The study was carried out between August 2007 and July 2009 at the Universiti Kebangsaan Malaysia Hospital and Faculty of Veterinary Universiti Putra Malaysia.